2022
DOI: 10.1002/dac.5383
|View full text |Cite
|
Sign up to set email alerts
|

Data‐centric approaches in the Internet of Vehicles: A systematic review on techniques, open issues, and future directions

Abstract: The Internet of Vehicles (IoV) is an emerging network of connected vehicles as a branch of dynamic objects in the Internet of Things (IoT) ecosystem. With the rapid development of IoV, real-time data-centric applications would be a significant concern in academia and industry to promote efficiency and realize modern services in such high dynamic networks. In this paper, we aim to present a systematic literature review (SLR) for the IoV networks to investigate the different attitudes in the field of data-centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Partovi et al (2023) suggested a thorough survey of data-centric approaches in the IoV network using SLR methodology. The authors aimed to provide a comprehensive overview of various techniques and methodologies used to manage and process data in the IoV ecosystem.…”
Section: Relevant Workmentioning
confidence: 99%
“…Partovi et al (2023) suggested a thorough survey of data-centric approaches in the IoV network using SLR methodology. The authors aimed to provide a comprehensive overview of various techniques and methodologies used to manage and process data in the IoV ecosystem.…”
Section: Relevant Workmentioning
confidence: 99%
“…1 Because of vehicles' considerable mobility and the specific environment of these networks, inter-vehicle communications (IVC) in these high-dynamic networks contrast with other types of wireless communications, in terms of trust, security, and privacy issues. [2][3][4][5] Network security is the process by which a network is secured against various internal and external threats. 6 With determining network assets and their threat factors, multiple risks should be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…IoV network efficiency is mainly affected by data handling strategies, network density variations, congestion problems, traffic jams, and specifically, security concerns 1 . Because of vehicles' considerable mobility and the specific environment of these networks, inter‐vehicle communications (IVC) in these high‐dynamic networks contrast with other types of wireless communications, in terms of trust, security, and privacy issues 2‐5 . Network security is the process by which a network is secured against various internal and external threats 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Internet of Vehicles (IoV) is referred to as Internet‐enabled VANETs, wherein vehicles share data gathered from smart devices and sensors to roadside units (RSUs) and processing infrastructures to aid in rapid decision‐making. IoV is a subcategory of the Internet of Things (IoT) ecosystem that benefits from generated information of connected vehicles 3–5 …”
Section: Introductionmentioning
confidence: 99%